Evaluating use of institutional repositories by lecturers in Nigerian universities (2017)
The study investigated use of Institutional Repositories (IRs) among lecturers in Nigerian Universities. It examined the level of awareness, frequency of use, preferred archiving method, purpose of use of IRs and challenges of use of IRs among lecturers. Five universities in Nigeria that had functional institutional repositories for at least three years as at 2015 were purposively selected. Five faculties were purposively selected from which 1151 lecturers were randomly selected. A structured questionnaire was used to collect data and descriptive statistics were used for data analysis. Findings revealed that majority of the lecturers were aware of IRs, they accessed materials from IRs on daily and weekly basis while they deposited their works into IR on annual and bi-annual basis. It was also revealed that lecturers preferred mediated archiving and they used materials from IRs to prepare lecture notes and research works. Fear of copyrights infringement, plagiarism and lack of awareness were major challenges of use of IRs. The study recommended that the university libraries should check the copyrights status of scholarly works to ensure non-infringement, organise more awareness programs on IRs and mediated archiving method should be used to encourage lecturers to submit their scholarly works